Forest Multifunctionality - Högbom, Lars; Jõgiste, Kalev; Kniivilä, Matleena; Lukmine, Diana; Mustonen, Mika; Rautio, Pasi; Samariks, Valters; Svensson, Johan; Vodde, Floortje; Zute, Daiga; Øistad, Knut (PROFOR network, 2023)
To meet all demands and challenges that we, as a society, exert on our forests, knowledge-based cross-sectorial interdisciplinary research is needed to move forward. Areas are becoming scarce; stakeholders are in conflict, but, multiple use approaches point at integration and synergy opportunities. Accordingly, there is an increasing need for science-based policy support for EU decision-making concerning multiple uses of forests. In the end, future-proofing Europe’s forest is an aspiration we all share.
Keywords: multiple use; forests